Age-associated changes in VO2 and power output - A cross-sectional study of endurance trained New Zealand cyclists - Brown, S. J.; Ryan, H.; Brown, J. A. (Journal of Sports Science & Medicine, 2007)
Age-associated changes in power and maximal oxygen consumption (VO2max) were studied in a cross section of endurance trained cyclists. Subjects (n = 56) performed incremental cycling exercise, during which capillary blood lactate [La-] was measured. Power output increased by 30 Watts during each 5 minutes stage, with initial power output based on individual ability. When [La-] was >4.5 mmol·L-1, subjects were given a 10 min recovery at a power output approximately 50% below estimated power at [La-]4mmol. Subjects then performed an incremental test (1 minute stages) to VO2max. Decline in VO2max was 0.65 ml·kg-1·min-1·year-1 (r = -0.72, p < 0.01) for males, and 0.39 ml·kg-1·min-1·year-1 (r = -0.54, p < 0.05) for females. Power at VO2max decreased by 0.048 W kg-1·year-1 (r = -0.72, p < 0.01) in males. Power at [La-]4mmol decreased by 0.044 W kg-1 year-1 (r = -0.76, p < 0.01) in males, and by 0.019 W kg-1·year-1 (r = -0.53, p < 0.05) in females. Heart rate at VO2max (HRmax) showed a weaker correlation with age in males (r = -0.36, p < 0.05). The age-associated changes in maximum aerobic power and sub-maximal power were gender- specific, thus suggesting different age-related effects on the systems which support exercise in males and females.